Public Debt Dynamics : The Effects of Austerity, Inflation, and Growth Shocks - Hasanov, Fuad (IMF Working Papers; Working Paper ;, 2012)
We study how macroeconomic shocks affect U.S. public debt dynamics using a VAR with debt feedback. Following a fiscal austerity shock, the debt ratio initially declines and then returns to its pre-shock path. Yet, the effect is not statistically significant. In a weak economic environment, the likelihood of a self-defeating austerity shock is much higher than in normal times. An inflation shock only slightly reduces the debt ratio for a few quarters. A positive growth shock unambiguously lowers debt. In our specification, the debt ratio is stationary, whereas a VAR excluding debt may imply an explosive debt path.